Long-Horizon direct model predictive control of an active capacitor for ripple energy compensation in single-phase DC-to-AC converters - Chingwena, Macyln (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.